Estimation of Serum Vitamin D, Calcium and Phosphorus in Chronic Kidney Disease - Rajbhandari, Ajay; Agrawal, Rajendra Kumar; Baral, Anil; Pokhrel, Anil; Shrestha, Dineshwori; Hada, Rajani (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Abnormalities in mineral metabolism are invariable with progressive deterioration of kidney function in chronic kidney disease (CKD). These abnormalities are documented in CKD on dialysis in our population but not on pre dialysis. So, present study aims to estimate serum vitamin D, calcium and phosphorus in CKD stage 3-5ND. Methods: It was a cross sectional study of established new CKD patients not on dialysis, vitamin D, calcium, phosphate binders and corticosteroids therapy. Blood sample was drawn for estimation of serum vitamin D, creatinine, calcium, phosphorus and albumin and CKD staging done by KDIGO (2012) criteria. SPSS software version 19 was used for data analysis and chi-squared and ANOVA test was applied as the test of significance. Results: Sixty six (51 male and 15 female) CKD patients with a mean age of 54.3±14.8 years were studied. Hypovitaminosis D (<30 ng/ml) was present in 84.8%, with deficiency (<20 ng/ml) in 50% and insufficiency (20-30) ng/ml in 34.8%. Other abnormalities observed were hypocalcemia (60.6%), hypercalcemia (1.5%) and hyperphosphatemia (63.6%) with no difference of corrected calcium, significant difference of serum phosphorus (p<0.001) with hyperphosphatemia in stage 4 and 5 CKD and vitamin D insufficiency in stage 3b, deficiency in stage 3a, 4 and 5 CKD. There was no correlation of serum vitamin D with calcium and phosphorus in different stages of CKD. Conclusion: Present study concludes that hypovitaminosis D, hypocalcemia and hyperphosphatemia is common in our pre-dialysis CKD patients and serum phosphorus raises more with reduction of GFR.